Lockdown effect of the brown dog tick with-in a bamboo sticky trap using sustained release pheromone beads in kennels. Issue 2 (17th February 2021) - Gowrishankar, S.; Latha, Bhaskaran Ravi; Sreekumar, C.; Leela, V.
ABSTRACT: Ticks are ubiquitous in nature and have considerable medical and veterinary importance. They act as vectors for a diverse array of pathogens affecting animals and humans. Rhipicephalus sanguineus is the most prevalent species infesting the dogs in Tamil Nadu. Control of this three-host tick mainly depends on the use of acaricides, with attendant problems of development of acaricidal resistance in ticks and possibility of drug residues. In the current study, pheromones were evaluated as an alternative substance for control of the dog tick. Optimal concentration of attractant sex pheromone (ASP), assembly pheromone (AP), and combination of both ASP and AP were encapsulated using calcium alginate beads for sustained release of pheromones. Bamboo sticky traps were designed as a platform to hold these pheromone encapsulated beads. Field trials were conducted using these pheromone lures as bait in the bamboo trap. Field trials revealed that AP encapsulated calcium alginate beads lured the maximum number of different stages of dog ticks. Thus, a bamboo trap with AP encapsulated calcium alginate beads can be used in integrated pest management along with other routine practices for control of dog tick in kennels. Statistical analysis by chi-square test revealed that there was a highly significant (p < 0.01) difference in the level of attraction between engorged and questing stages of ticks to the pheromones in the trap.